Keamanan Komunikasi Data Pada Jaringan Komputer Berbasis Socket Programming - Siahaan, R. Fanry; Smangunsong, Agustina; Febrian, Ibnu; Putri, Widia (Universitas Sari Mutiara Indonesia Medan, 2022)
A socket is software used to communicate data between computers on a network, which is a combination of an IP (Internet Protocol) address and a port number. In data communication on a computer network, one of the important things that are lacking attention and understanding from users is information security, both in terms of information content and communication lines. So without realizing it that the communication lines used have been infiltrated by other people. Because one of the loopholes that can be exploited in infiltrating other people's networks is a socket on the network. One way or method of securing communication lines on a network is socket programming. Socket Programming is a protocol that makes connections between devices in a network so that one program can interact with other programs in a network.